2016
DOI: 10.1038/ncomms13019
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tubulin drugs conjugated to anti-ErbB antibodies selectively radiosensitize

Abstract: Tumour resistance to radiotherapy remains a barrier to improving cancer patient outcomes. To overcome radioresistance, certain drugs have been found to sensitize cells to ionizing radiation (IR). In theory, more potent radiosensitizing drugs should increase tumour kill and improve patient outcomes. In practice, clinical utility of potent radiosensitizing drugs is curtailed by off-target side effects. Here we report potent anti-tubulin drugs conjugated to anti-ErbB antibodies selectively radiosensitize to tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 47 publications
1
42
0
Order By: Relevance
“…However, one main problem of radiation therapy is that some cancer cells are refractory to the treatment. To improve efficacy, chemotherapy is often administered during radiation therapy to sensitize the cancer cells (known as chemoradiation therapy) 6366 . However, the trade-off of the accompanying chemotherapy is increased systemic toxicity and even increased mortality 67 .…”
Section: Key Concepts and The Status Quomentioning
confidence: 99%
“…However, one main problem of radiation therapy is that some cancer cells are refractory to the treatment. To improve efficacy, chemotherapy is often administered during radiation therapy to sensitize the cancer cells (known as chemoradiation therapy) 6366 . However, the trade-off of the accompanying chemotherapy is increased systemic toxicity and even increased mortality 67 .…”
Section: Key Concepts and The Status Quomentioning
confidence: 99%
“…Free payloads used in the antibody‐drug conjugate (ADC) technology such as maytansinoids or auristatins are efficient radiosensitizers, but with high off‐target side effects. ADCs that target EGFR or HER2 efficiently radiosensitize esophageal, gastric, head and neck tumor cells . However, clinical trials that tested the combination of anti‐EGFR or HER2 antibodies with gemcitabine for patients with pancreatic cancer did not find any additional benefit compared to gemcitabine alone, thus limiting the use of such antibodies for ADC‐induced radiosensitization in PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…3 Reducing tumor radioresistance, limiting the exposure of the surrounding normal tissues, and improving tumor control are the major goals to improve radiotherapy efficiency in cancer. Free payloads used in the antibody-drug conjugate (ADC) technology such as maytansinoids or auristatins are efficient radiosensitizers, 4,5 but with high off-target side effects. ADCs that target EGFR or HER2 efficiently radiosensitize esophageal, gastric, head and neck tumor cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the clinical utility of potent radiosensitizing drugs is limited by their side effects in practice. There is a recent study reported potent anti-tubulin drugs conjugated to anti-ErbB antibodies; one of them, namely as T-DM1 selectively radiosensitize tumours based on surface receptor expression [2]. The authors showed that concurrent use of T-DM1 with RT prolongs tumour control in tumours overexpressing HER2.…”
mentioning
confidence: 99%